E-005 Preliminary result of carotid artery stenting using angioguard XP/precise stent with technique of mild post-angioplasty. (16th November 2010) - Fujii, M; Uemura, A; Matsukawa, H; Yamamoto, D; Kobayashi, N; Numaguchi, Y; Murakata, A; Shinoda, M; Ishikawa, R
Abstract : Carotid artery stenting (CAS) using Angioguard XP/Precise stent (AG/PS) has been widely used for treating carotid artery stenosis. However, the use of this device was considered to cause a relatively high occurrence rate of embolic complications compared with the use of other off labeled occlusion or protection devices. One of the reasons is thought to be the excessive pressing on the atheroma plaque lesion post-angioplasty after stenting. Here, we report the preliminary results of CAS with AG/PS using mild post-angioplasty (mild post-PTA) in a small number of patients at our institution. CAS was successfully performed in 12 patients (men, 11; women, one; average age 70.6 years; six patients under general anesthesia) using this technique over a 10 month period. Eight patients showed symptomatic carotid artery stenosis. The preoperative carotid artery average per cent stenosis by NASCET criteria was 73.8%. Furthermore, we discuss the postoperative carotid artery per cent stenosis, cerebral ischemic complication, other complication events, no flow/slow flow event and carotid artery restenosis rate. The postoperative carotid artery average per cent stenosis was improved to 7.5%. Moreover, good dilatation was achieved after stenting using mild post-PTA. Postoperative diffusion weighted MR images showed high intensity spotty lesions. One patient (8.3%) presented with motor speech disturbance and asymptomatic no flow event. Perioperative complication and carotid artery restenosis after stenting have not occurred so far during a short follow-up period, indicating a relatively acceptable result of CAS with AG/PS using mild post-PTA. Other procedures to achieve good stenting results using mild post-PTA are needed, as well as data from long term follow-up at our own institution.